Career trajectories of AB sociology graduates of Xavier University - Abuso, Ma. Rhea Gretchen A. (Philippine Sociological Review, 2018)
A college degree is a sought-after qualification for job-seekers in the Philippines. Most departments that offer a sociology degree program will tout job prospects in research and teaching—career possibilities that aside from not being an exclusive field for sociologists, is not exactly considered as “in-demand” or “prestigious.” Propelled by the belief that a sociology degree can lead to job prospects outside teaching and research, this report documents career trajectories of AB Sociology graduates of Xavier University in Cagayan de Oro. This study documented sociology graduates who found employment in various sectors such as in the corporate sector, communications, and government service and who affirmed the relevance and appropriateness of their sociology degree in their respective occupations.